Language Politics of Regional Integration - Morris, Michael A. author. aut Link
X, 214 p.
Keywords: Language policies are politically sensitive in impacting, either positively or negatively, language choice, language prestige, and language spread. Rising regional integration, both formal and informal, adds to the sensitivity and complexity of language politics, whether in North America, South America or Europe. Language Politics of Regional Integration: Cases from the Americas shows how language politics vary across the region and contrast with language politics in Europe. Morris presents a framework for systematically comparing selected cases from the Americas by distinguishing between eight different dimensions of language politics. These are then applied to case studies of Canada, the United States, Mexico, Central America, and the Caribbean. The book concludes by identifying in each case particularly divisive issues as well as opportunities for promoting reconciliation.